Intermediate E-F layer dynamics study in the Brazilian low-latitude sector: observational data and simulations - Muella, Marcio T. A. H.; Silva, Ana P. M.; Santos, Ângela M. dos; Pillat, Valdir G.; Resende, Laysa C. A.; Andrioli, Vânia F.; Fagundes, Paulo R. (Frontiers in Astronomy and Space Sciences, 2024)
This study investigates the downward motion of Intermediate E-F Layers (ILs) in the Brazilian low latitude sector through observation and modeling. Ionosonde data from São José dos Campos (SJC) and Palmas (PAL) were analyzed to investigate the seasonal variation of the IL parameters, including the virtual height (h'IL) and the top frequency (ftIL). The ILs primarily originated from F layer detachment followed by downward motion, peaking before 11 LT and disappearing well before sunset. Daily height variability ranged between 130 and 190 km, with peak frequencies around 4–5 MHz. Using meteor radar data as input, the Ionospheric E-region Model (MIRE) simulated diurnal and semidiurnal tides to analyze neutral wind effects on ILs descent. Model simulations for SJC (October 2008) and PAL (April and June 2009) revealed distinct wind oscillations influencing IL dynamics at heights below 140 km. In SJC, meridional wind shears controlled IL descent, with possible zonal wind interactions weakening ILs. Conversely, in PAL during April 2009, both zonal and meridional winds contributed to IL formation and altitude descent. However, discrepancies between observed and modeled descent rates suggest the need for considering additional atmospheric wave interactions in future modeling studies. June 2009 over PAL presented unique IL behavior, exhibiting a lower observed decay rate and daily height oscillations potentially linked to local modulations. Meanwhile, MIRE indicated that meridional wind shearing predominantly controlled IL descent in the morning, with zonal wind becoming relevant post-midday. These findings enhance our understanding of IL dynamics and their atmospheric drivers.